Motives for Texting During Early Adolescence - Yau, Joanna C.; McPartlan, Peter; Reich, Stephanie M. (Frontiers in Human Dynamics, 2021)
Research on adolescent texting has largely focused on whether the frequency of texting is associated with well-being. Whether the motives for texting is associated with well-being is not well known. We surveyed 130 young adolescents (Mage = 12.41 years) and identified user-clusters based on their motives for texting. We then examined whether the clusters were associated with phone habits that may affect health and learning (e.g., phone placement when sleeping). Participants were asked how often they texted someone when they were excited, proud, frustrated, angry, anxious, sad, needed help with homework, wanted to make plans, and needed advice [0 (never) to 4 (always)]. Using k-means clustering, we identified six clusters. On one end of the continuum were Frequent-Texters and Positive-Frequent-Texters. Frequent-Texters texted often for all purposes and Positive-Frequent-Texters frequently texted for all purposes except expressing negative emotions. On the other end of the continuum were Selective-Texters and Positive-Selective-Texters. Selective-Texters rarely texted for any reason and Positive-Selective-Texters rarely texted except for expressing positive emotions. In between were the Moderate-Texters and the Positive-Practical-Moderate-Texters. Moderate-Texters texted less frequently than Frequent-Texters and more frequently than Selective-Texters for all purposes. Positive-Practical-Moderate-Texters texted more frequently than Moderate-Texters for positive emotions and for practical reasons. Clusters differed by gender, texting experience, and Fear of Missing Out (FOMO). Frequent-Texters started texting at a marginally younger age than Selective-Texters, had high FOMO scores, and were all girls. Clusters also differed in their phone habits. For instance, when sleeping, Frequent-Texters were more likely than other groups to have their phones on or next to the bed. When doing homework, Selective-Texters were less likely to keep their phones on or near them. Interestingly, Positive-Frequent-Texters were more likely to have the ringer on or to have their phone on vibrate while doing homework, but not more likely to keep their phones nearby. Given that texting is a common communication method, it is important to understand the heterogeneity of reasons why youth text and how those reasons relate to phone habits.